Electronegative very-low-density lipoprotein induces brain inflammation and cognitive dysfunction in mice - Ying-Shao Lin (Nature Portfolio, 2021)
Abstract Epidemiologic studies have indicated that dyslipidemia may facilitate the progression of cognitive dysfunction. We previously showed that patients with metabolic syndrome (MetS) had significantly higher plasma levels of electronegative very-low-density lipoprotein (VLDL) than did healthy controls. However, the effects of electronegative-VLDL on the brain and cognitive function remain unclear. In this study, VLDL isolated from healthy volunteers (nVLDL) or patients with MetS (metVLDL) was administered to mice by means of tail vein injection. Cognitive function was assessed by using the Y maze test, and plasma and brain tissues were analyzed. We found that mice injected with metVLDL but not nVLDL exhibited significant hippocampus CA3 neuronal cell loss and cognitive dysfunction. In mice injected with nVLDL, we observed mild glial cell activation in the medial prefrontal cortex (mPFC) and hippocampus CA3. However, in mice injected with metVLDL, plasma and brain TNF-α and Aβ-42 levels and glial cell activation in the mPFC and whole hippocampus were higher than those in control mice. In conclusion, long-term exposure to metVLDL induced levels of TNF-α, Aβ-42, and glial cells in the brain, contributing to the progression of cognitive dysfunction. Our findings suggest that electronegative-VLDL levels may represent a new therapeutic target for cognitive dysfunction.